The Image of Magical Clothes in English Wonder Tales - Djurabayevna, Djumayeva Nozima (Miasto Przyszłości, 2023)
The article discusses specific features of magical clothes used in English fairy tales. Their magic features, descriptions and how they are linked with the dreams of people and their thoughts, tabooes are given. The national life of each nation is reflected in its clothing culture. Clothes are a special external protector of the human body. They protect a person from hot and cold weather and rain. Therefore, in folk tales, the image of magical clothes has been artistically interpreted as a protector. Dressing allows people to identify themselves socially, sexually, morally, aesthetically. Magical clothes, and the recognition that they are woven or sewn from magical fabrics, have long been characteristic of folklore.